«Alliance of Psychology, Psychotherapy and Pharmacotherapy. Science and the real world in the treatment of mental disorders» - article Editorial (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2021)
Resolution of the conference dedicated to the 90th anniversary of the birth of B.D. Karvasarsky.